Development model of food self-sufficient program based on the assistance of agriculture extension, poor households, and aid types in South Sumatra, Indonesia - Darwan Agus; Sriati Sriati; Riswani Riswani; Dedik Budianta (Heritage and Sustainable Development)
The food self-sufficient South Sumatra program aimed to change the society's mindset from buying to producing their own food, especially to meet their own needs, such as vegetables, chicken, and fish by optimizing their home yards or vacant land for production. There are main factors that influence the achievement of food self-sufficiency program, namely internal and external factors originating from agriculture extension, poor households, and aid types provided. The study aimed to formulate a development model for food self-sufficient program in South Sumatra based on the assistance of agriculture extension, poor households, and aid types. The research used a survey method with a sample collection using a disproportionate stratified random sampling method. The sample was 144 samples, consisting of 24 agriculture extension and 120 poor households received aid. The results showed that the development strategy of the food self-sufficient program in South Sumatra was in quadrant I (positive, positive). It means that the strengths and opportunities greater than the weaknesses and threats. The formulated strategies based on SWOT analysis were: (1) improve the quality and quantity of agriculture extension to households, (2) provide the required aid, (3) empower productive poor households, and (4) making high farming experience a guarantee in maintaining the aid until it produces, thus meeting daily needs, especially for vegetables, chicken, and/or fish.